2018
DOI: 10.1002/jcb.27965
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Wharton's jelly extracellular matrix as a promising scaffold for promoting hepatic differentiation of human induced pluripotent stem cells

Abstract: Liver tissue engineering as a therapeutic option for restoring of damaged liver function has a special focus on using native decellularized liver matrix, but there are limitations such as the shortage of liver donor. Therefore, an appropriate alternative scaffold is needed to circumvent the donor shortage. This study was designed to evaluate hepatic differentiation of human induced pluripotent stem cells (hiPSCs) in decellularized Wharton's jelly (WJ) matrix as an alternative for native liver matrix. WJ matric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…It has been demonstrated that DWJM is able to retain many chemotactic factors and soluble bioactive factors positively affecting cell viability and function (Basiri et al, 2019). Therefore, for these different reasons DWJM has been proposed as potential therapeutic agent in many areas (Jadalannagari et al, 2017;Kehtari et al, 2019;Li et al, 2019). A still unexplored field is represented by the degenerated IVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that DWJM is able to retain many chemotactic factors and soluble bioactive factors positively affecting cell viability and function (Basiri et al, 2019). Therefore, for these different reasons DWJM has been proposed as potential therapeutic agent in many areas (Jadalannagari et al, 2017;Kehtari et al, 2019;Li et al, 2019). A still unexplored field is represented by the degenerated IVD.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the abundance of hyaluronic acid (HA) makes this tissue strongly hydrated, viscous and suitable as potential substitute of NP (Jadalannagari et al, 2017;Bullard et al, 2019). In addition, WJ, being rich in growth factors and cytokines (Penolazzi et al, 2010;Jadalannagari et al, 2017;Najar et al, 2018;Kehtari et al, 2019) is particularly attractive for potential application in tissue engineering (Beiki et al, 2017;Basiri et al, 2019;Li et al, 2019;Walker et al, 2019). In recent years, different methods to decellularize the WJ have been developed and compared, aimed at producing a scaffold able to sustain cell viability and proliferation, and preserve the native ECM microstructure and secretion profile (Stocco et al, 2014;Beiki et al, 2017;Jadalannagari et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Kehtari et al [109] proposed a protocol for obtaining hepatic differentiation of hiPSCs seeded on decellularized Wharton jelly (DWJ) scaffolds as an alternative scaffold for circumventing donor shortage. Cell volume increased significantly after differentiation, showing the typical morphological characteristics of hepatocytes.…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…5 Biomaterials can be divided into natural compounds including hydroxyapatite (Ha), gelatin, collagen, chitosan, etc. [8][9][10] and synthetic ceramics such as poly-L-lactide acid (PLLA), poly caprolactone (PCL), and poly lactide acid (PLA), etc. [11][12][13][14] The compatibility issue can be avoided by using electrospinning technology, in which the polymeric solutions are transformed into nanofibers by electrostatic forces.…”
Section: Introductionmentioning
confidence: 99%